Students’ Knowledge on Topic and their Ability to Write - Ayu Rizki Septiana (STKIP PGRI Tulungagung, 2020)
This study was aimed to investigate the correlation between students’ knowledge on topic to be written and their ability to write. The writing course for the second semester students of English Department of STKIP PGRI Tulungagung is Academic Reading and Writing. In this course, the students should be able to develop their competence in reading academic essays as well as composing the essays using the correct organization. However, it has been observed that their ability to write the essays are in relation with their knowledge on the topic to be written. From the findings, it can be concluded that the hypothesis can be accepted since the statistical analysis using Kendal Tau showed that the coefficient of the correlation was positive medium correlation 0.473 and the correlation was significant (0.016 0.05). Therefore, it can be concluded that there is significant correlation between students’ knowledge on topic to be written and their writing ability and the students with better knowledge on topics also have better writing ability.